A two-layer skin construct consisting of a collagen hydrogel reinforced by a fibrin-coated polylactide nanofibrous membrane - Bacakova, Marketa; Pajorova, Julia; Broz, Antonin; Hadraba, Daniel; Lopot, Frantisek; Zavadakova, Anna; Vistejnova, Lucie; Beno, Milan; Kostic, Ivan; Jencova, Vera; Bacakova, Lucie (International journal of nanomedicine, 2019)
Background: Repairs to deep skin wounds continue to be a difficult issue in clinical practice. A promising approach is to fabricate full-thickness skin substitutes with functions closely similar to those of the natural tissue. For many years, a three-dimensional (3D) collagen hydrogel has been considered to provide a physiological 3D environment for co-cultivation of skin fibroblasts and keratinocytes. This collagen hydrogel is frequently used for fabricating tissue-engineered skin analogues with fibroblasts embedded inside the hydrogel and keratinocytes cultivated on its surface. Despite its unique biological properties, the collagen hydrogel has insufficient stiffness, with a tendency to collapse under the traction forces generated by the embedded cells. Methods: The aim of our study was to develop a two-layer skin construct consisting of a collagen hydrogel reinforced by a nanofibrous poly-L-lactide (PLLA) membrane pre-seeded with fibroblasts. The attractiveness of the membrane for dermal fibroblasts was enhanced by coating it with a thin nanofibrous fibrin mesh. Results: The fibrin mesh promoted the adhesion, proliferation and migration of the fibroblasts upwards into the collagen hydrogel. Moreover, the fibroblasts spontaneously migrating into the collagen hydrogel showed a lower tendency to contract and shrink the hydrogel by their traction forces. The surface of the collagen was seeded with human dermal keratinocytes. The keratinocytes were able to form a basal layer of highly mitotically-active cells, and a suprabasal layer. Conclusion: The two-layer skin construct based on collagen hydrogel with spontaneously immigrated fibroblasts and reinforced by a fibrin-coated nanofibrous membrane seems to be promising for the construction of full-thickness skin substitute.
Keywords: Mitochondria; novorozenec; Infant, Newborn; Humans; Polyesters; membrány umělé; hydrogely; Keratinocytes; Skin, Artificial; keratinocyty; krysa rodu Rattus; Dermis; lidé; mitochondrie; kolagen; zvířata; proliferace buněk; Nanofibers; Collagen; nanovlákna; pohyb buněk; polyestery; Cell Proliferation; Membranes, Artificial; Cell Movement; škára; Hydrogels; Rats; fibroblasty; Animals; Fibrin; fibrin; Fibroblasts; umělá kůže